The Illusion of Supremacy: a Theory of Indifference - Hoft, Joseph (Criminology, criminal justice, law & society, 2023)
The Supremacy Clause establishes that federal law takes precedence over conflicting state law and can consequently nullify state legislation. However, the inconsistent enforcement of the Supremacy Clause regarding the coexistence of conflicting state and federal cannabis laws raises questions about the legitimacy of the federal government. By drawing on the contrasting views of social conflict theory and consensus theory, a new indifference theory better encompasses the rare phenomenon of the federal government choosing not to invoke the Supremacy Clause when it has the means to. This highlights the potential for delegitimization in the federal government due to the inconsistency in enforcing the Supremacy Clause, leading to the public’s potential noncompliance of federal law. The federal government must address these inconsistencies to retain a strong legitimate legal system.